An Augmented Reality (AR) indoor navigation mobile application for the Faculty of Information and Communication Technology (FICT) - Goh, Brian Joon Jian (2024)
Outdoor navigation applications have been widely used nowadays, with the help of GPS technology these outdoor navigation application able to help users to navigate through the streets easily even not knowing the place. However, there is not much indoor navigation application in the market, as GPS signal does not work effectively indoor. Moreover, much hardware installation is needed to build an indoor navigation system. Hence the aim of this project is to develop an AR indoor navigation application that helps the students at University Tunku Abdul Rahman to find their way when first entering the vast compound of UTAR Kampar. The application created from this project will also help the student to know the purpose of certain room such as lecture hall, tutorial class and so on to prevent students from walking into the wrong classroom. The application uses AR technology to provide the user with accurate direction and information about the classroom and buildings. AR technology is used to ensure that user had an immersive navigation experience compared with traditional 2-D map. A few existing applications on the market will be reviewed and methodology to develop this application will be provided.